2022
DOI: 10.11591/ijece.v12i2.pp1558-1564
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of resting electroencephalogram coherence in patients with mild cognitive impairment and normal elderly subjects

Abstract: Mild cognitive impairment (MCI) was a condition beginning before more serious deterioration, leading to Alzheimer’s dementia (AD). MCI detection was needed to determine the patient's therapeutic management. Analysis of electroencephalogram (EEG) coherence is one of the modalities for MCI detection. Therefore, this study investigated the inter and intra-hemispheric coherence over 16 EEG channels in the frequency range of 1-30 Hz. The simulation results showed that most of the electrode pair coherence in MCI pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Coherence measurements in the Alzheimer’s dataset have been reported in a previous study [ 38 ]. The coherence calculations results show that the MCI group’s coherence is lower than the normal elderly subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Coherence measurements in the Alzheimer’s dataset have been reported in a previous study [ 38 ]. The coherence calculations results show that the MCI group’s coherence is lower than the normal elderly subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of coherence changes in the control and chiropractic groups shows that the inter-hemispheric coherence changes in all frequency bands are significantly different between the two groups. Research has shown that EEG inter-hemispheric coherence is significantly lower in patients with AD and MCI than in controls ( Zheng-yan, 2005 ; Hadiyoso et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-hemispheric coherence analysis showed a significant reduction in the connection of the frontal-temporal-central-occipital network, which was found significantly in the pair of electrodes containing FP1. Decreased intrahemispheric coherence in MCI patients is related to the disconnection of cortico-cortical connectivity which connects the temporoparietal, and occipital areas with the frontal areas ( Hadiyoso et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This real dataset was created to aid researchers working on EEG motion artifact reduction techniques by allowing them to compare and contrast existing methods as well as develop new models. Hadiyoso et al [15] presented a study comparing the coherence of EEG signals in mild cognitive impairment (MCI) patients and healthy people. Its goal is to make each group's feature visible so that the coherence value can be used to detect early Alzheimer's disease via EEG analysis.…”
Section: Electroencephalography Signalmentioning
confidence: 99%